The Evolving Role of Marketing in Supply Chain Management: A Comprehensive Bibliometric Review - Susantinah , Nugrahini; Handriana, Tanti; Leilasariyanti, Yennyka; Sangadji, Suwandi S.; Rahindra, Hendy Arsyaf (Journal of Posthumanism, 2025)
This study investigates the evolving relationship between marketing and supply chain management (SCM) through a comprehensive bibliometric review. The primary objective is to analyze how these disciplines have intertwined over time, identify key authors and influential publications, explore emerging research themes, and reveal existing gaps in the literature. Utilizing a bibliometric approach, the research involved systematic data collection from the Scopus database, focusing on peer-reviewed articles published between 2020 and 2024. The analysis employed software tools such as VOSviewer and BibExcel for publication frequency, citation impact, co-citation, and thematic mapping. The findings indicate a significant integration of marketing and SCM, driven by the need for cohesive strategies to align operations with customer satisfaction in the context of global complexities. Key themes identified include the role of artificial intelligence (AI), blockchain technology, sustainability, and environmental innovation, which are pivotal in enhancing responsiveness and decision-making within supply chains. Influential authors, such as Ahluwalia et al. and Toorajipour et al., have contributed substantially to this discourse. The study also highlights emerging trends, particularly the impact of digitalization on consumer interactions and marketing logistics. Ultimately, the research underscores the critical need for further exploration of the interconnections between marketing and SCM to address contemporary challenges and inform future strategies.